Tìm x biết:
(3x - 1)3 = -8
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(3^x+3^{x+1}=3^8.2+2.3^8.2017^0\)
\(3^x+3^x.3=3^8.2^2\)
\(3^x=3^8.2^2:3\)
\(3^x=3^7.2^2\)
3x+3x+1=38.2+2.38.201703x+3x+1=38.2+2.38.20170
3x+3x.3=38.223x+3x.3=38.22
3x=38.22:33x=38.22:3
3x=37.223x=37.22
a: \(x^3-4x^2-x+4=0\)
=>\(\left(x^3-4x^2\right)-\left(x-4\right)=0\)
=>\(x^2\left(x-4\right)-\left(x-4\right)=0\)
=>\(\left(x-4\right)\left(x^2-1\right)=0\)
=>\(\left[{}\begin{matrix}x-4=0\\x^2-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=4\\x^2=1\end{matrix}\right.\Leftrightarrow x\in\left\{2;1;-1\right\}\)
b: Sửa đề: \(x^3+3x^2+3x+1=0\)
=>\(x^3+3\cdot x^2\cdot1+3\cdot x\cdot1^2+1^3=0\)
=>\(\left(x+1\right)^3=0\)
=>x+1=0
=>x=-1
c: \(x^3+3x^2-4x-12=0\)
=>\(\left(x^3+3x^2\right)-\left(4x+12\right)=0\)
=>\(x^2\cdot\left(x+3\right)-4\left(x+3\right)=0\)
=>\(\left(x+3\right)\left(x^2-4\right)=0\)
=>\(\left(x+3\right)\left(x-2\right)\left(x+2\right)=0\)
=>\(\left[{}\begin{matrix}x+3=0\\x-2=0\\x+2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-3\\x=2\\x=-2\end{matrix}\right.\)
d: \(\left(x-2\right)^2-4x+8=0\)
=>\(\left(x-2\right)^2-\left(4x-8\right)=0\)
=>\(\left(x-2\right)^2-4\left(x-2\right)=0\)
=>\(\left(x-2\right)\left(x-2-4\right)=0\)
=>(x-2)(x-6)=0
=>\(\left[{}\begin{matrix}x-2=0\\x-6=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=2\\x=6\end{matrix}\right.\)
Tìm x biết
1. 2(5x-8)-3(4x-5)=4(3x-4)+11
2. (2x+1)2-(4x-1).(x-3)-15=0
3. (3x-1).(2x-7)-(1-3x).(6x-5)=0
1) \(\Rightarrow10x-16-12x+15=12x-16+11\)
\(\Rightarrow14x=4\Rightarrow x=\dfrac{2}{7}\)
2) \(\Rightarrow4x^2+4x+1-4x^2+13x-3-15=0\)
\(\Rightarrow17x=17\Rightarrow x=1\)
3) \(\Rightarrow\left(3x-1\right)\left(2x-7+6x-5\right)=0\)
\(\Rightarrow\left(2x-3\right)\left(3x-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{3}{2}\\x=\dfrac{1}{3}\end{matrix}\right.\)
2: Ta có: \(\left(2x+1\right)^2-\left(4x-1\right)\left(x-3\right)-15=0\)
\(\Leftrightarrow4x^2+4x+1-4x^2+12x+x-3-15=0\)
\(\Leftrightarrow17x=17\)
hay x=1
`x . 3/7 = 2/3`
`=>x= 2/3 : 3/7`
`=>x= 2/3 . 7/3`
`=>x=14/9`
`-----------`
`x : 8/11 = 11/3`
`=>x= 11/3 . 8/11`
`=>x= 88/33`
`=>x=8/3`
`-----------`
`4/7 . x - 2/3 = 1/5`
`=> 4/7 . x = 1/5 +2/3`
`=>4/7 . x =3/15 + 10/15`
`=>4/7 . x =13/15`
`=>x= 13/15 : 4/7`
`=>x= 13/15 xx 7/4`
`=>x= 91/60`
Lời giải:
$x.\frac{3}{7}=\frac{2}{3}$
$x=\frac{2}{3}: \frac{3}{7}=\frac{14}{9}$
-----------
$x: \frac{8}{11}=\frac{11}{3}$
$x=\frac{11}{3}.\frac{8}{11}=\frac{8}{3}$
-----------
$\frac{4}{7}x-\frac{2}{3}=\frac{1}{5}$
$\frac{4}{7}x=\frac{2}{3}+\frac{1}{5}=\frac{13}{15}$
$x=\frac{13}{15}: \frac{4}{7}=\frac{91}{60}$
a)
\(|3x+1|=4\)
\(\Rightarrow\orbr{\begin{cases}3x+1=4\\3x+1=-4\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}3x=4-1\\3x=-4-1\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}3x=3\\3x=-5\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=3\div3\\x=-5\div3\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=1\\x=-1,6667\end{cases}}\)
Vậy x = 1
(3x-1).(2x+3)-x(6x-8) = 7
(6x2+9x-2x-3)-(6x2-8x)=7
6x2-6x2+9x-2x+8x-3=7
15x-3=7
15x=7+3
x= 10:15
x= \(\frac{2}{3}\)
Giải:
a) \(\dfrac{-5}{6}-x=\dfrac{7}{12}+\dfrac{-1}{3}\)
\(\dfrac{-5}{6}-x=\dfrac{1}{4}\)
\(x=\dfrac{-5}{6}-\dfrac{1}{4}\)
\(x=\dfrac{-13}{12}\)
b) \(2.\left(x-\dfrac{1}{3}\right)=\left(\dfrac{1}{3}\right)^2+\dfrac{5}{9}\)
\(2.\left(x-\dfrac{1}{3}\right)=\dfrac{1}{9}+\dfrac{5}{9}\)
\(2.\left(x-\dfrac{1}{3}\right)=\dfrac{2}{3}\)
\(x-\dfrac{1}{3}=\dfrac{2}{3}:2\)
\(x-\dfrac{1}{3}=\dfrac{1}{3}\)
\(x=\dfrac{1}{3}+\dfrac{1}{3}\)
\(x=\dfrac{2}{3}\)
c) \(\left|2x-\dfrac{3}{4}\right|-\dfrac{3}{8}=\dfrac{1}{8}\)
\(\left|2x-\dfrac{3}{4}\right|=\dfrac{1}{8}+\dfrac{3}{8}\)
\(\left|2x-\dfrac{3}{4}\right|=\dfrac{1}{2}\)
\(\Rightarrow\left[{}\begin{matrix}2x-\dfrac{3}{4}=\dfrac{1}{2}\\2x-\dfrac{3}{4}=\dfrac{-1}{2}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{5}{8}\\x=\dfrac{1}{8}\end{matrix}\right.\)
d) \(\dfrac{2}{3}x+\dfrac{1}{6}x=3\dfrac{5}{8}\)
\(x.\left(\dfrac{2}{3}+\dfrac{1}{6}\right)=\dfrac{29}{8}\)
\(x.\dfrac{5}{6}=\dfrac{29}{8}\)
\(x=\dfrac{29}{8}:\dfrac{5}{6}\)
\(x=\dfrac{87}{20}\)
Xét : \(x>\frac{3}{2}\) ta có :
\(2x-3+3x-1=8\Leftrightarrow5x-4=8\Rightarrow x=\frac{12}{5}\)(TM)
Xét \(\frac{1}{3}\le x\le\frac{3}{2}\) ta có :
\(3-2x+3x-1=8\Leftrightarrow2+x=8\Rightarrow x=6\left(l\right)\)
Xét \(x< \frac{1}{3}\) ta có :
\(3-2x+1-3x=8\Leftrightarrow4-5x=8\Rightarrow x=-\frac{4}{5}\)(TM)
Vậy \(x=\left\{-\frac{4}{5};\frac{12}{5}\right\}\)
(3x-1)3=-8
(3x-1)3=(-2)3
3x-1 =-2
3x =-2-1
x =(-3):3
x =-1.
(3x-1)3=-8
<=>3x-1=-2
<=>x=-1
Vậy..............